Genomic Insight Into the Population Structure and Admixture History of Tai-Kadai-Speaking Sui People in Southwest China - Bin, Xiaoyun; Wang, Rui; Huang, Youyi; Wei, Rongyao; Zhu, Kongyang; Yang, Xiaomin; Ma, Hao; He, Guanglin; Guo, Jianxin; Zhao, Jing; Yang, Meiqing; Chen, Jing; et al. (Frontiers in Genetics, 2021)
Sui people, which belong to the Tai-Kadai-speaking family, remain poorly characterized due to a lack of genomic-wide data. To infer the fine-scale population genetic structure and putative genetic sources of the Sui people, we genotyped 498,655 genome-wide single nucleotide polymorphisms (SNPs) using SNP-arrays in 68 Sui individuals from seven indigenous populations in Guizhou province and Guangxi Zhuang Autonomous Region in Southwest China and co-analyzed with available East Asians via a series of population genetic methods including principal component analysis (PCA), ADMIXTURE, pairwise Fst genetic distance, f-statistics, qpWave, and qpAdm. Our results revealed that Guangxi and Guizhou Sui people showed a strong genetic affinity with populations from southern China and Southeast Asia, especially Tai-Kadai and Hmong-Mien speaking populations as well as ancient Iron Age Taiwan Hanben, Gongguan individuals, supporting Sui people came from southern China originally. The indigenous Tai Kadai-related ancestry (represented by Li), Northern East Asian-related ancestry and Hmong-Mien-related lineage contributed to the formation processes of the Sui people. We identified the genetic substructure within Sui groups: Guizhou Sui people were relatively homogeneous, possessed the similar genetic profiles with neighboring Tai-Kadai related populations, such as Maonan. While Sui people in Yizhou and Huanjiang of Guangxi might receive unique, additional gene flow from Hmong-Mien speaking populations and Northern East Asians respectively after the divergence within other Sui populations. Sui people could be modeled as the admixture of ancient Yellow River Basin farmer-related ancestry (36.2%~54.7%) and ancient Coastal Southeast Asian-related ancestry (45.3%~63.8%). We also identified the potential positive selection signals related to the disease susceptibility in Sui people via iHS, nSL scores. These genomic findings provided new insights into the demographic history of Tai-Kadai speaking Sui people and their interaction with neighboring populations in Southern China.